The Outsiders are the Map: Travel Narratives of Central American Migrants on Mexico’s Southern Border - Rodrigo Parrini Roses; Edith Flores Pérez (Íconos)
This article analyses the ways in which Central American migrants travelling through Mexico to reach the United States make oral maps to orient themselves during their journeys. These migrants, often fleeing poverty and violence, travel through Mexico in very irregular ways, such as on cargo trains or on-foot, and find themselves in a state of high vulnerability. Many of these travelers do not have access to printed or digital maps and as a result must rely on oral maps that the migrants create through their multiple attempts to cross the northern border into the United States. These oral maps narrate their journeys and in particular help to navigate specific parts of their journeys to the northern border. However, these maps do not estimate how long specific legs of the trip will take and thus the migrants experience a dislocated sense of temporality during their travels.